ANALISIS PERBANDINGAN RENCANA ANGGARAN BIAYA (RAB) PEKERJAAN PELAT BETON KONVENSIONAL DAN PELAT BETON BOUNDECK - ZAEDAR GAZALBA; I GEDE PUTU WARKA (GANEC SWARA, 2022)
The development of construction technology is currently experiencing rapid progress which is characterized by the presence of various types of modern materials and equipment, especially in the field of construction. With the increasingly rapid technological advancements in the field of construction, the innovations that have been raised are floor plate systems using boundeck, which is another alternative to conventional plates. Therefore, it is necessary to conduct analytical research to determine the efficiency of the use of the boundeck concrete plate method on concrete slab work, when compared to the use of conventional methods, both in terms of cost, time and method of implementation.The results showed that: (1) The cost of boundeck concrete plate formwork was 51% cheaper than conventional concrete plates; (2) The cost of fixing boundeck concrete plates is 56% cheaper than conventional concrete plates; (3) Casting costs 18% cheaper than conventional concrete plates; (4) Cost of boundeck concrete plate material is 43% cheaper than conventional concrete plates; (5) The cost of the boundeck concrete plate worker wages is 12% cheaper than conventional concrete plates; (6) The cost of renting boundeck concrete plates is 46% cheaper than conventional concrete plates; (7) The duration of implementation of boundeck concrete plates is 32% faster than conventional concrete plates; (8) Recapitulation of the cost of boundeck concrete plates is 41% cheaper than conventional concrete plates; (9) Boundeck concrete plates produce less waste material compared to conventional concrete plates; (10) Procurement of boundeck concrete plate material is more difficult than conventional concrete plates. Based on these ten (10) aspects, the boundeck concrete plate method is more recommended for concrete slab work.